INHIBITORY CONTROL AND EMPATHY: A STUDY OF SMOKING IN PUBLIC PLACES AMONG STUDENTS - Thalib, Tarmizi; Satriana; Nurhikmah (Journal Of Nursing Science Research, 2025)
Smoking behavior in public places is often found in various places, but rarely discussed in terms of inhibitory control and empathy. This study aims to determine the relationship of inhibitory control with empathy for smokers in public places in students in Makassar. The type of research used in this study is quantitative. The sample in the study was smoker students who were in Makassar. This research was conducted on 301 student smokers in Makassar. The results of the hypothesis test analysis found r (12) = -.732, p = .00. which shows the relationship between inhibitory control and empathy for smokers in public places in students in Makassar with a negative direction. This study expects the students to be more considerate of cigarette consumption in public places and understand the principle of empathy for themselves and others.